1968
DOI: 10.1139/p68-138
|View full text |Cite
|
Sign up to set email alerts
|

The mass distributions of meteoroids and asteroids

Abstract: A theory of the mass distribution of interplanetary particles has been developed and it has been shown that, provided the solid debris resulting from the erosion due to mutual collisions is not important, then the asymptotic mass distribution is a power law. The predictions of this theory are compared with observations, and very good agreement is found in the case of meteor streams and asteroids > 2km in diameter. For sporadic meteoroids it was found that a second process was needed to explain the observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1970
1970
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Typical meteor trails are an order of magnitude larger than the first Fresnel zone and hence the scattering point may fall randomly along the ionization profile, depending on the scattering geometry. In a statistical sense, it has been previously shown (Jones 1968;McIntosh & Simek 1969;Blaauw et al 2011;) that the amplitude distribution can be used as a proxy for the initial meteoroid mass such that the distribution of radar echo amplitudes follows…”
Section: Measuring Meteoroid Mass Indices With Radar: Theoretical Conmentioning
confidence: 99%
See 4 more Smart Citations
“…Typical meteor trails are an order of magnitude larger than the first Fresnel zone and hence the scattering point may fall randomly along the ionization profile, depending on the scattering geometry. In a statistical sense, it has been previously shown (Jones 1968;McIntosh & Simek 1969;Blaauw et al 2011;) that the amplitude distribution can be used as a proxy for the initial meteoroid mass such that the distribution of radar echo amplitudes follows…”
Section: Measuring Meteoroid Mass Indices With Radar: Theoretical Conmentioning
confidence: 99%
“…The net effect is that the measured mass index is lower than the true mass index. Both Jones (1968) and McIntosh & Simek (1969) recognized this bias and attempted to make corrections based on estimates of the initial radius that was then available and assuming single body ablation. They found that in some cases the correction from apparent to true mass index could be as much as +0.5, a significant difference.…”
Section: Measuring Meteoroid Mass Indices With Radar: Theoretical Conmentioning
confidence: 99%
See 3 more Smart Citations